Controversial Issues in the Life of the Hungarian-origin Consort of the Last Khedive of Egypt and Sudan: نقاط جدلية في حياة زوجة آخر خديوي مصري ذات الأصل المجري - Al-Naggar, Abdallah Abdel-Ati; Prantner, Zoltán (Études sur la Région Méditerranéenne, 2022)
Not many people know that Abbas Helmy II, the last Khedive of Egypt and Sudan, had a Hungarian consort, Countess May Török Szendrői, who was known after her marriage and conversion to Islam as Djavidan Hanem. Their love-based marriage and life, full of hardships and tribulations, sparked many speculations, and as a result led to misconceptions about May. Conflicting information has already appeared about her name, exact date of birth and origin. Here, our main goal is to dispel the errors and misconceptions referring to scientifically accepted archival and documentary sources. In this piece, we also intend to prove that the father of the Khediva of the Nile is the famous Hungarian inventor Tivadar Puskás and not the Count József Török Szendrői.